Mental Retardation in Algerian Educational System - SEGHIER, Fatiha (My University, 2017)
This study addressed the issue of children with developmental disability by examining the challenges faced by teachers who teach children with developmental disability and how they try to overcome these challenges. The present study is divided into three main chapters. The first chapter is lliterature review which presents a review of related literature that provides different definitions of disability. The second chapter is devoted to the field of work which describes the findings and data analysis, the findings and discussion of findings. The third chapter shed the light about some suggested recommendations for improving teachers’ awareness about the mental retardation through the help of parents. Teachers in this study expressed the need for reduced class sizes, modern teaching materials, motivations to teachers, and additional support services from the government. Most teachers teaching children with developmental disability did not receive any special needs education training from the university, they feel that they are not qualified to teach the children with developmental disability.
(Case Study: Educational Medical Centers for Mentally Retarded Children of RELIZANE)
Keywords: Children desability; Teachers challenge; Psychology; Education